CRITERIA OF THE RETURN TO SPORT AFTER RECONSTRUCTION OF THE ANTERIOR CRUCIATE LIGAMENT - Eddine, Hussein Alaa; Kanso, Hassan; Ziab, Houssein; Eddine, Hassane Kheir; Karaki, Hassan; Khoury, Alfred; Hassan, Khodor Haidar (European Scientific Journal, ESJ, 2015)
Background: Despite the progress of reconstruction techniques for the anterior cruciate ligament (LCA), the return to sport after this surgery remains a challenge. The absence of good knowledge in the measures of appropriate results after ACL rehabilitation can lead the patients to return to play prematurely, making them in front of a high risk of injury again later. Over one-third of athletes are unable to resume their sport at the same level and almost one fifth will suffer from new accident during this recovery, either on the operated knee or contralateral knee. While the fear of another accident remains the biggest obstacle to return to sport, persistent functional deficits is the leading cause of recurrence tear. Objective: to conduct an environmental study of clinical practice surgeons and physiotherapists decision making in the return to sport (RTS) after ACL ligament; and to gain a better understanding of how clinicians take the suitable decision to back to the sport. Participants: 34 physiotherapists and 11 orthopedic surgeons are included in this study. Interventions: Lebanese surgeons and physiotherapists completed distinct and validated questionnaires which consisted of 10 closed questions, each including a sections on demography, outcome measurement, treatment and procedures including the decisions of the RTS. Data collection: The main measures were the descriptive and subjective collected from orthopedic surgeons and physiotherapists. The use of measures of clinical outcomes by the two groups is qualitatively analyzed for similarities between the professions and criteria recently proposed consensus used to decide the RTS. The level of agreement for the definition of success for the RTS following a ligamentoplasty ACL was explored by the frequency of response for each item. Results: Analysis of the results show that 90% of participants consider that physiotherapists have a vital role in the decision making to return to sport after ACL reconstruction. In addition, several measurement scales are mostly used for evaluation of ACL as the jump test, Lachman test, pain ... while the analysis of the Pearson correlation between the number of patients taken by year and the criteria of success of the decision to return to ground shows a very weak correlation (P <0.452), which reflects the poor experience of Lebanese physiotherapists in the selection of the factors influencing the return to sport. Conclusion: The results show a lack of scientific knowledge in the participants on valid tests that can be used for clinical decision-making to return to sport after ACL reconstruction. Future studies are recommended to verify these results with a large number of participants.